Estimating total microplastic loads to the marine environment as a result of ship biofouling in-water cleaning - Soon, Zhi Yang; Tamburri, Mario N.; Kim, Taekhyun; Kim, Moonkoo (Frontiers in Marine Science, 2024)
The widespread use of polymers across various industries has led to significant microplastic pollution in marine environments, with millions of tons of microplastics being released annually. This study examines the contribution of coatings particles released from commercial ships, to marine microplastic pollution. Key sources of these microplastics include the weathering and abrasion of coatings during ship maintenance activities. Marine coatings, which are rich in polymers such as polyurethanes and epoxies, are released into the ocean through processes like normal wear and tear, damage, in-water cleaning, and removal of old paint layers. Our research indicates that the global shipping sector could be a substantial contributor to microplastic pollution, potentially releasing thousands of tons annually. Predictive modeling identifies bulk carriers as the largest contributors, followed by tankers, containerships, and cargo vessels. This study also finds that manual biofouling cleaning by divers generates more microplastics than cleaning using mechanized in-water cleaning (IWC) systems with debris capture. Mitigation strategies, such as alternative cleaning methods and improved waste capture and processing, are proposed, but their effectiveness remains uncertain due to implementation challenges. A multidisciplinary approach and coordinated global efforts are essential to develop effective strategies for reducing microplastic pollution from ship coatings and protecting marine ecosystems.